PENGARUH LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Indeks Kompas100 yang Terdaftar di Bursa Efek Indonesia Tahun 2019–2021) - Emila Ajie Widyasari; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
This research refers to research by Affianti (2017) that examines the effect of good corporate governance, firm size, leverage, and profitability on accounting conservatism level in banking industry. This research aims to examine the effect of leverage, liquidity, and profitability in applying accounting conservatism to financial reports issued by companies. The variables used in the research are leverage, liquidity, and profitability as independent variables, as well as accounting conservatism as a dependent variable. Secondary data is used in this research and purposive sampling is used as the sampling technique. The difference between this research and the previous one is that the sample used in this research is index Kompas100 companies listed on Indonesian Stock Exchange in 2019–2021 with the total samples being 129 samples. Data analysis uses IBM SPSS 26 to identify the effect of leverage, liquidity, and profitability on accounting conservatism.The research results show that leverage have a significant positive effect on accounting conservatism. Meanwhile, the liquidity variable has no effect on accounting conservatism. Research also proves that profitability has a significant positive effect on accounting conservatism.